Estimation of direct evaporation from groundwater by using lysimeters in the Salar de Pedernales basin, Chilean Altiplano - Payano-Almánzar, Reynaldo; Dionizis, Dimitri (Acta Universitaria, 2020)
In this research an estimation of the evaporation discharges from shallow groundwater in the Salar de Pedernales basin is made, using the lysimeter methodology. The analysis performed shows values between 1400 L·s-1 and 1900 L·s-1 with an uncertainty of error of 5% with respect to the average and between 11% and 47% in relation to the minimum and maximum values which can be compared by other studies where different tools have been used to calculate evaporation, such as: chamber, numerical model, water balance, Bowen relationships, Eddy correlations, and evaporation curves vs. altitude. The results confirm that lysimeters are appropriate tools for the determination of soil evapotranspiration and evaporation from shallow groundwater, whose components are key in the hydrology of endorheic basins, arid and semi-arid zones, for the management of protected natural spaces such as salt flats, waterholes, fertile plains, and bofedales.